Pengaruh Likuiditas, Leverage, Ukuran Perusahaan dan Kepemilikan Institusional Terhadap Kinerja Keuangan Perusahaan Kesehatan - Musa Budiarta Gunawan; Suryani Suryani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This Research was conducted aiming to determine the effect of liquidity, leverage, firm size and institusional ownership on financial performance.the population in this study is 33 health sector companies listed on the Indonesian Stock Exchange. By using the purposive sampling method, a sample of 13 companies was obtained. The analytical tool used is multiple linear regression analysis using the Statistical Product and Service Solution (SPSS) Version 22 Program. The result of this study indicate that liquidity have a positive and significant effect on financial performance, leverage have a negative and significant effect on financial performance while firm size and institusional ownership have no effect on financial performance.